2017
DOI: 10.18632/oncotarget.23098
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autophagic flux and its related inflammation in patients with adult-onset Still’s disease

Abstract: The pathogenic role of autophagic immune regulation in adult-onset Still’s disease (AOSD) is unclear. We investigated the relative levels of autophagy in AOSD patients and healthy controls, its association with disease activity or course, and the change in autophagy after 6 months of therapy. Autophagosome levels were determined from the mean fluorescence intensity of autophagosomotropic dye incorporated into circulating immune cells. The fluorescent signal from lymphocytes, monocytes, and granulocytes from AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…The ATG16L1 gene on 2q37.1 encodes a short coiled-coil protein that interacts with ATG5 and ATG12 to form a 350-kDa multimeric complex that plays a crucial role in autophagosome formation [15]. Consistent with this finding, our previous study revealed increased levels of the autophagosome, ATG, and LC3-II expression in patients with AOSD compared with controls [8]. In the present study, the frequencies of the GG/TT/CC or AG/CT/CT haplotype of ATG16L1 in patients with AOSD were significantly different from those of controls, suggesting that ATG16L1 gene polymorphisms are associated with AOSD susceptibility.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The ATG16L1 gene on 2q37.1 encodes a short coiled-coil protein that interacts with ATG5 and ATG12 to form a 350-kDa multimeric complex that plays a crucial role in autophagosome formation [15]. Consistent with this finding, our previous study revealed increased levels of the autophagosome, ATG, and LC3-II expression in patients with AOSD compared with controls [8]. In the present study, the frequencies of the GG/TT/CC or AG/CT/CT haplotype of ATG16L1 in patients with AOSD were significantly different from those of controls, suggesting that ATG16L1 gene polymorphisms are associated with AOSD susceptibility.…”
Section: Discussionsupporting
confidence: 64%
“…Regarding its functional association, lower mRNA expression levels of LC3-II and ATG16L1 were noted in patients with AOSD carrying the AA/CC/TT haplotype than in those with the AGCTCT plus GGTTCC haplotype. Given that ATG16L1 deficiency induces IL-1β and IL-18 production [37], patients with AOSD carrying the AA/CC/TT haplotype may have impaired autophagy and consequently high-grade systemic inflammation, as demonstrated by our recent study [8]. However, our results should be validated in large cohorts of patients with AOSD of different ethnicities.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Further experimentation is needed to determine how specific learning activities affect the survival of each cell type and if the mitigation of increased neuron survival will impact cognitive processes. Due to the Ferrari et al, 2006;Shaftel et al, 2008;Hewett et al, 2012;Crews, 2012;Wu et al, 2013;Lin and Edelson, 2017;Pawley et al, 2020 Wang et al, 2013;Wang et al, 2019;Pehote and Vij, 2020 Mitochondria ↑ (↑ synaptogenesis,↑ neuron differentiation,↑ neuron maturation) Agnihotri et al, 2017;Arrázola et al, 2019;Khacho et al, 2019 NF-κ B ↑ ↓ (↓ NSC proliferation) Iosif et al, 2006;Koo et al, 2010;Chen and Palmer, 2013;Fernandez-Lizarbe et al, 2009;Yao et al, 2013 Wang et al, 2013Wang et al, , 2019Hsieh et al, 2017;Vij et al, 2018;Lambelet et al, 2018;Pehote and Vij, 2020 Hedgehog signaling ↑ (↑ NPC proliferation) Lai et al, 2003;Komada et al, 2008 The arrows show changes (↑: increase; ↓: decrease) in inflammation and hippocampal neurogenesis. The factors are labeled in respect to their positive (green) or negative (red) influence on hippocampal neurogenesis.…”
Section: Roles Of Hippocampal Neurogenesismentioning
confidence: 99%
“…Although autophagosomes accumulate after SCI (Zhang et al, 2014;Muñoz-Galdeano et al, 2018), autophagy flux in the spinal cord is impaired (Liu S. et al, 2018). Impaired autophagy flux, which can induce neurodegeneration (Hara et al, 2006;Komatsu et al, 2006;Liu S. et al, 2015), has been implicated to cause inflammation and autoimmune disorders in many disease models (Hsieh et al, 2017;Lambelet et al, 2018;Vij et al, 2018), especially in neurogenerative diseases (Nixon, 2013). Using the FIP200 knockdown model for studying autophagy, Wang et al found autophagy improves NSC survival, proliferation and differentiation into neurons, assists with NSC maintenance, and overall increases adult neurogenesis (Wang et al, 2013).…”
Section: Alteration Of Debris Removal Autophagy and Intracellular Processes After Chronic Scimentioning
confidence: 99%